2010
DOI: 10.1016/j.molcel.2010.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interplay of the Noncoding RNA ANRIL and Methylated Histone H3 Lysine 27 by Polycomb CBX7 in Transcriptional Silencing of INK4a

Abstract: SUMMARY Expression of the INK4b/ARF/INK4a tumor suppressor locus in normal and cancerous cell growth is controlled by methylation of histone H3 at lysine 27 (H3K27me) as directed by the Polycomb group proteins. The antisense non-coding RNA ANRIL of the INK4b/ARF/INK4a locus is also important for expression of the protein-coding genes in cis, but its mechanism has remained elusive. Here we report that chromobox 7 (CBX7) within the Polycomb Repressive Complex 1 binds to ANRIL, and both CBX7 and ANRIL are found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
1,133
8
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,247 publications
(1,191 citation statements)
references
References 51 publications
32
1,133
8
8
Order By: Relevance
“…Multiple single nucleotide polymorphisms (SNPs) of ANRIL, such as rs6475606, rs10757274 and rs2383206, were reckoned as the pathological factors for CAD, and CAD was observably affected by the aberrant expression of ANRIL 25. It was additionally demonstrated that ANRIL could recruit CBX7 of polycomb repressive complex 1 (PRC1) and suz12 of PRC2 within prostate tissues and fibroblasts, so that expressions of INK4b/ARF/INK4a locus would be restrained 31, 32. The CDKN2A/B therein encoded cell cycle regulatory proteins, such as p16 INK4A and p15 INK4B ,32 suggesting that ANRIL was actively involved in modifying cell proliferation, motility and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple single nucleotide polymorphisms (SNPs) of ANRIL, such as rs6475606, rs10757274 and rs2383206, were reckoned as the pathological factors for CAD, and CAD was observably affected by the aberrant expression of ANRIL 25. It was additionally demonstrated that ANRIL could recruit CBX7 of polycomb repressive complex 1 (PRC1) and suz12 of PRC2 within prostate tissues and fibroblasts, so that expressions of INK4b/ARF/INK4a locus would be restrained 31, 32. The CDKN2A/B therein encoded cell cycle regulatory proteins, such as p16 INK4A and p15 INK4B ,32 suggesting that ANRIL was actively involved in modifying cell proliferation, motility and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…33 Though it is still not fully understood how ANRIL functions, evidence suggests that this lncRNA may participate in the regulation of histone methylation. 34 Another lncRNA, MIAT (myocardial infarction-associated transcript) (or Gomafu/RNCR2) was identified as a risk factor associated with patients with myocardial infarction. 35 However, how MIAT controls the status of myocardial infarction remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the severity of atherosclerosis with ANRIL expression has been described 39,42) . Yap et al found that knockdown of ANRIL was associated with increased cyclin-dependent kinase inhibitors 2A (CDKN2A) expression and decreased H3K27me3 43) . However, Kotake et al showed that ANRIL knockdown by shRNA resulted in increased CDKN2B expression by disturbing SUZ12 binding to the Chr9p21 locus 44) .…”
Section: Long Noncoding Rnas Regulate the Function Of Ecsmentioning
confidence: 99%
“…However, Kotake et al showed that ANRIL knockdown by shRNA resulted in increased CDKN2B expression by disturbing SUZ12 binding to the Chr9p21 locus 44) . There are conflicts regarding CDKN2A or CDKN2B expression mediated by ANRIL knockdown, the significant decrease of cell proliferation, which play a key role in atherogenesis were observed [43][44][45] . Moreover, Holdt et al found that Alu motifs are essential for the pro-atherogenic functions of ANRIL.…”
Section: Long Noncoding Rnas Regulate the Function Of Ecsmentioning
confidence: 99%